SCS (SEMARANG-CHERIBON STOOMTRAM MAATSHAPPIJ) NETWORK ALONG THE NORTH COAST OF JAVA SEMARANG-CIREBON 1895-1942 - Ninda Lutfianti; Abdul Wahid (Satmata: Journal of Historical Education Studies, 2023)
This article analyzes the role of the Kamer van Koophandel en Nijverheid te Padang (Chamber of The limited transportation infrastructure along the North Coast of Java, stretching from Semarang to Cirebon, led to the emergence of transportation modernization in the form of a railway system. The introduction of railways was followes by various entities opening concessions for railroads in several areas of the Ducth East Indies. This will focus on NV.SCS as a private steam tram company that established its concession in the North Coast of Java region from Semarang to Cirebon, with a spesific emphasis on the network distributin created by this company. The research methodology employed in this study is a historical research method related to systematic procedures, processes, and techniques in descriptive analysis to obtain the subject under investigation. As a result, the network established by NV.SCS in divided into several areas, including the    Central North Coast of Java, the North Coast of Cirebon, and connectivity to the post. The rail lines constructed by NV.SCS were not limited to the main Semarang-Cirebon route but also extended into its branches into the surrounding inliand areas.